THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN ACTUALIZING TOLERANCE ATTITUDES TO STUDENTS - Fahmi Eko Saputro (STAI Hubbulwathan Duri, 2020)
The purpose of this study is to find out the role of the teacher of Islamic religious education in actualizing the tolerance attitude to the students and how the tolerance of the students. This research uses descriptive qualitative method with data collection such as observation, interviews, and documentation. The results of this study are, First, the role of teachers in instilling an attitude of tolerance towards students, namely acting as an informator, motivator, director, facilitator and evaluator that aligns with tolerance material. Second, the tolerance of students in this case, namely the attitude of tolerance towards friends, the attitude of tolerance towards teachers, the attitude of tolerance towards the school community and the attitude of tolerance towards parents.